2021
DOI: 10.1080/1359866x.2021.1978390
|View full text |Cite
|
Sign up to set email alerts
|

Arduous admissions and a precarious profession: student teachers’ pre-admission demotives

Abstract: Sustaining the attractiveness of the teaching profession to recruit committed students to teacher education is a global policy issue. However, in many parts of the world, the teaching profession has become less attractive. Also in Finland, where teacher education has traditionally been highly attractive, several programmes have recently suffered from a substantial decrease in the number of applicants. The current paper addresses the phenomenon by investigating student teachers' pre-admission demotives. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Precarity usually refers to a situation of "generalized insecurity" resulting from the disappearance of "full-time, predictable, unionized, and stable livelihoods" (Means, 2022, p. 1,360). As evident from a number of studies, teaching has not remained immune to the process of casualization (Ivancheva, 2015;Cuervo and Chesters, 2019;Melville et al, 2019;Rey et al, 2020;Stacey et al, 2022), In countries such as Finland, where teachers are highly valued professionals, the appeal of teaching career seems to be declining (Mankki and Kyrö-Ämmälä, 2022). The precarity of teachers in developing countries is, however, not well studied.…”
Section: Introductionmentioning
confidence: 99%
“…Precarity usually refers to a situation of "generalized insecurity" resulting from the disappearance of "full-time, predictable, unionized, and stable livelihoods" (Means, 2022, p. 1,360). As evident from a number of studies, teaching has not remained immune to the process of casualization (Ivancheva, 2015;Cuervo and Chesters, 2019;Melville et al, 2019;Rey et al, 2020;Stacey et al, 2022), In countries such as Finland, where teachers are highly valued professionals, the appeal of teaching career seems to be declining (Mankki and Kyrö-Ämmälä, 2022). The precarity of teachers in developing countries is, however, not well studied.…”
Section: Introductionmentioning
confidence: 99%
“…Keck Frei et al (2017) concluded that working with children and young people was the most important predictor of choosing the teaching profession as a career for males. Mankki and Kyrö-Ämmälä (2021) found that the most demotivating reasons for teacher candidates before their entry into the profession were the difficulties of being accepted, the challenges of the profession, limited career opportunities, the dilemma of vocational programs offering insufficient diversity, insecure careers, and the media as a source of demotivation. Mašková et al (2022) found that the highest motivation category was a love for children and a desire to work with them, followed by supporting the education journey of others, the meaningfulness of the teaching profession, the perception of it as a secure profession, its ability to make a social contribution, and a love for the profession.…”
Section: Introductionmentioning
confidence: 99%